Ответы и объяснения

2012-07-14T10:53:12+04:00

Найдем ОДЗ:

x²-4x+3≥0;

x²-5x+4≥0;

 

(x-1)(x-3)≥0;

(x-1)(x-4)≥0;

 

x≤1 или x≥3;

x≤1 или x≥4;

 

xє(- ∞;1]U[4;+∞)


\sqrt{x^2-4x+3}<\sqrt{x^2-5x+4}+1; x^2-4x+30; D=256-144=112; x1=(8+2\sqrt{7})/3, x2=(8-2\sqrt{7})/3; x<(8-2\sqrt{7})/3 x>(8+2\sqrt{7})/3

Ответ:x<(8-2\sqrt{7})/3 </p>&#10;<p>x>(8+2\sqrt{7})/3

2012-07-14T11:13:52+04:00

Решение:

√(x²-4x+3) - √(x²-5x+4)=0;

Объеденим в систему уравнений,зная что подкоренное выражение ≥0:

{x²-4x+3≥0;

{x²-5x+4≥0;

По теореме Виета находим корни:

{(x-1)(x-3)≥0;

{(x-1)(x-4)≥0;

 

{x≤1 или x≥3;

{x≤1 или x≥4;

 

xє(- ∞;1]U[4;+∞);


√(x²-4x+3)<√(x²-5x+4)+1;

x²-4x+30;

D=256-144=112=2√7;

x₁=(8+2√7)/3;

x₂=(8-2√7)/3;

x<(8-2√7)/3>(8+2√7)/3